Development of Ethno-Vlog Integrated E-LKPD on Chemical Reaction Equations to Enhance Students’ Scientific Literacy and Creative Thinking Skills - Putra Reinho Rosario Sanam; Agung Tri Prasetya; Harjono Harjono (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang, 2025)
This study aimed to develop and evaluate an Integrated Ethno-Vlog E-LKPD (Electronic Student Worksheet) to enhance students’ scientific literacy and creative thinking skills in chemistry learning. The research used a Research and Development (R&D) approach, employing a modified 3D model of Thiagarajan’s 4D development, consisting of the definition, design, and development stages. The study involved 36 students from Grades X and XI at SMAK St. Gabriel Noemuti as participants. Data collection techniques included questionnaires, interviews, classroom observations, expert validations of content and media, and pretest-posttest assessments of scientific literacy and creative thinking. Quantitative analysis was conducted using pretest, posttest, and N-Gain scores to measure learning outcomes. The results showed that the average scientific literacy score was 81.43, with an N-Gain of 0.63, categorized as moderate, while the average creative thinking score was 81%, indicating a notable improvement. The integration of local wisdom through Ethno-Vlog videos in the E-LKPD helped students connect chemical concepts, particularly chemical reaction equations, with real-life phenomena in their surrounding environment. These findings suggest that the Integrated Ethno-Vlog E-LKPD is effective in supporting students’ understanding, fostering scientific literacy, and enhancing creative thinking skills, providing a promising approach for contextual and culturally relevant science learning